Concept of Gender and Mathematics Education Conceito de Gênero e Educação Matemática - Maria Celeste Reis Fernandes de Souza; Maria da Conceição Ferreira Reis Fonseca (Universidade Estadual Paulista, 2009)
The text presents the emergence of the concept of gender in education, showing its different nuances, and proposes its incorporation as a category of analysis in the field of Mathematics Education, in which the discussions on gender are rarely detected, especially when we analyze the Brazilian production. Taking as references the female scholars in the field of gender studies, we have reflected on the need of incorporating such concept into the investigation about the processes of teaching and learning Mathematics, the subjects in the pedagogical relations, and the cultural mode of conceiving, using and evaluating mathematical knowledge. Such incorporation would imply, however, the disruption in the ways in which we have thought concepts related to female, male and mathematics. Keywords: Gender. Mathematics Education. Research. O texto expõe a emergência do conceito de gênero no campo da educação, mostrando suas diferentes nuances, e propõe sua incorporação como uma categoria de análise no campo da Educação Matemática, no qual as discussões sobre gênero aparecem muito raramente, especialmente quando se analisa a produção brasileira. Tomando como referência estudiosas do campo dos estudos de gênero, refletimos sobre a necessidade da incorporação de tal conceito às investigações sobre os processos de ensino e aprendizagem da Matemática, sobre os sujeitos das relações pedagógicas e sobre os modos culturais de se conceber, utilizar e avaliar conhecimentos matemáticos. Tal incorporação implicaria, porém, deslocamentos nos modos como temos pensado femininos, masculinos e matemática. Palavras-chave: Gênero. Educação Matemática. Pesquisa.